An Analysis Of Illocutionary Act Used by Main Characters Of Bang Ijal TV Comedy Video In Instagram - Yonita, Annissa Fitri; Refnaldi, Refnaldi (English Language and Literature, 2021)
In language study, peech act is the act when someone does speech to show the meaning by the speakers when communication occurs. Speech acts also can be analyzed from video that found in movie, talk show, stand up comedy, comedy video. Illocutionary acts is the utterence that force the listener to do something. In this research focuses with illocutionary acts produced by the main characters in Bang Ijal TV videos. The purpose of this research are to describe the types of illocutionary acts and the function of illocutionary acts used by each main character in the video which is downloaded from Instagram based on theory of Searle. The type of the research in this study are qualitative and quantitative research. Qualitative research is used to analyze the data in the form text and the quantitative act is used to calculatethe number of illocutionary acts and function of illocutionary acts used in Bang Ijal TV videos to conclude which type of illocutionary acts is dominantly used. This study found that there are five types of illocutionary acts and also 26 functions of illocutionary act. This study shows, the dominant illocutionary is directives which total persentage 43.83% and the dominant function of illocutionary acts is asking which total persentage 27.16%.